2016
DOI: 10.18535/jmscr/v4i6.34
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices in A Well Baby Clinic of A Tertiary Hospital in North Kerala

Abstract: To study the infant feeding practices among mothers accompanying infants in a well baby clinic. To evaluate the association between educational status and religion of mother and the feeding practice. Methods: A clinic based cross-sectional descriptive study among mothers accompanying infants for immunization and check up during a period of six months. Data was collected using a pre tested questionnaire Results: A total of 432 mothers and their infants were enrolled in the study. 19.8% of infants were given pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Madhu K et al (19%) and Mallikarjun et al (19.5%) also demonstrated similar practice of prelacteal feeding in their studies. [18][19][20][21] The most common prelacteal feed used was sugar water, honey which was found to be similar to a study by Madhu K et al 20 In the present study as many as 30.9% of the mothers had breastfeeding problems during their stay in the hospital. This is comparable to another study conducted by Suksham J et al who showed that 35.7% of the mothers had breastfeeding problems, where both term and preterm babies were included in the study population.…”
Section: Discussionsupporting
confidence: 85%
“…Madhu K et al (19%) and Mallikarjun et al (19.5%) also demonstrated similar practice of prelacteal feeding in their studies. [18][19][20][21] The most common prelacteal feed used was sugar water, honey which was found to be similar to a study by Madhu K et al 20 In the present study as many as 30.9% of the mothers had breastfeeding problems during their stay in the hospital. This is comparable to another study conducted by Suksham J et al who showed that 35.7% of the mothers had breastfeeding problems, where both term and preterm babies were included in the study population.…”
Section: Discussionsupporting
confidence: 85%